A rare unusual location of neuroblastoma in the anterior-middle mediastinum in infant: A case report and literature review - Quynh Giang Nguyen, MD; Duy Ngo Quang, MD; Van Manh Trinh; Dinh Huy Phan; Thi Hang Nguyen, MD; Thi Thuy Linh Nguyen, MD (Radiology Case Reports)
Neuroblastoma is a common tumor in children; however, its occurrence in the mediastinum - particularly in the anterior-middle mediastinum - is rare. Early diagnosis is crucial to initiate timely treatment and prevent disease progression. Surgery and chemotherapy are the standard treatments for neuroblastoma. Neuroblastoma should be considered in the differential diagnosis of anterior-middle mediastinal masses in children.